Basic income: a guide for the open-minded - Standing, Guy (New Haven, 2017)
"Shouldn’t everyone receive a stake in society's wealth? Could we create a fairer world by guaranteeing income to all? What would this mean for our health, wealth, and happiness? Basic income is a revolutionary idea that guarantees regular, unconditional cash transfers from the government to all citizens. It is an acknowledgement that everyone plays a part in generating the wealth currently enjoyed by only a few and would rectify the recent breakdown in income distribution. Political parties across the world are now adopting this innovative policy and the idea generates headlines every day. Guy Standing has been at the forefront of thought surrounding basic income for the past thirty years, and in this book he covers in authoritative detail its effects on the economy, poverty, work, and labor; dissects and disproves the standard arguments against basic income; explains what we can learn from pilots across the world; and illustrates exactly why basic income has now become such an urgent necessity."